The Relationship Between Chinese Students Sports Activities and Adaptation to University Life - Jinlong Wang; 박순문 (International Journal of Advanced Culture Technology(IJACT), 2024)
South Korea is experiencing a decline in its population due to a decreasing birth rate, which is leading to a reduction in the number of educated people. In response, the country is actively working to attract international students. On the other hand, China, with its geographical proximity and similar cultural background, tends to prefer studying in South Korea, which offers a scientific and systematic education system. The purpose of this study is to investigate the relationship between friendship and adjustment to university life according to the purpose of studying abroad among Chinese students who are engaged in sports activities. Therefore, the subject of the study was to set the population of Chinese students who are engaged in sports activities in Korea. The sampling method was convenience sampling, and a total of 300 copies of data were sampled through sharing the questionnaire link online and via email. The survey tool used was a questionnaire, which was modified and supplemented based on a questionnaire whose reliability and validity were recognized in previous studies. Statistical analysis used for data analysis was performed according to the purpose of analysis using SPSS Windows 20.0 Version. The conclusions obtained in this study through data analysis according to these methods and procedures are as follows. First, it was found that there is a partial difference in friendship among Chinese students who participate in daily sports depending on the purpose of their study abroad. Second, it was found that there is a partial difference in the adjustment of Chinese students to university life according to the purpose of studying abroad for Chinese students who participate in daily physical education. Third, it was found that the friendship of Chinese students who participate in daily sports has a partial influence on their adaptation to university life.